167 VOLATILE ORGANIC COMPOUND PROFILING FOR DETECTION OF ESOPHAGEAL CANCER IN EXHALED BREATH. (14th September 2020) - Vissapragada, R; Dharmawardhana, N; Watson, D; Yazbek, R
Abstract:  : Endoscopic surveillance for Barrett's esophagus (BE) is invasive but remains the standard modality for early diagnosis of esophageal adenocarcinoma (EAC) and intervention. Human breath contains an array of volatile organic compounds (VOC) that change in disease conditions. VOC detection provides a potential source of biomarkers for non-invasive, real-time identification of EAC. This study aimed to characterize a VOC-profile applicable to the detection of EAC and to provide pilot data to design a future validation trial. Methods: Breath samples were collected in our endoscopy unit from BE, EAC, and control patients. Samples were collected in FlexFoil bags (SKC ltd) using previously standardized methods. Hydrogen, methane and other VOCs were quantified by QuinTron BreathTracker® and selected-ion flow tube mass spectrometry (SIFT-MS, Syft®) respectively. 250 reported cancer-related VOCs were selected for analysis. Non-parametric tests were used to identify candidate VOCs, and logistic regression analysis was then applied to determine the best predictors for EAC. Receiver Operating Characteristic (ROC) Curves were developed to determine the sensitivity and specificity of the model. Results: 68 individuals were enrolled in the study (Controls, n = 37; BE, n = 21; EAC, n = 10). 8 VOCs were identified with significant concentration differences between the three groups: Trimethylbenzene (3 iso-forms), Dimethyl Sulfide, 4-isopropyl toluene, 1-butanol, trichloroethylene, hydrogen sulfide, methyl mercaptan, p-isopropenyl toluene. Logistic regression analysis of these 10 compounds demonstrated predictive probability of EAC from other groups with ROC curves calculating an area under the curve of 0.85. Conclusion: Previous studies have supported the utility of VOCs in exhaled breath as non-invasive real-time tests for the identification of some other cancer types. This pilot study has identified potential VOCs which might identify individuals with EAC. A larger study will be needed to validate and confirm these findings.